The rebirth of psychedelic therapy: An integrative literature review (Research, Society and Development, 2021)
Objective: This study is a general approach to psychedelic science and aims, from an integrative literature review, to contextualize the rebirth of psychedelic therapy. Methodology: By searching the electronic database Medical Publications (PubMed) and the Scientific Electronic Library (Scielo) with the descriptor in English: "psychedelic therapy", the articles that make up this work were selected. The research was conducted between January and May 2021. The inclusion criteria used were articles in English and Portuguese, published in the last 20 years and related to the research question. Results: 43 articles were found in the search in the databases. However, only 7 articles were selected for analysis according to the inclusion criteria. Conclusion: After analyzing the texts, it was possible to correlate several aspects and conclude that there are great perspectives and potentials in psychedelic therapy and that its rebirth takes place in a context of social transformations and unmet demands in psychotherapy.